A prospective study of focal brain atrophy, mobility and fitness. (11th April 2019) - Tian, Q.; Resnick, S. M.; Davatzikos, C.; Erus, G.; Simonsick, E. M.; Studenski, S. A.; Ferrucci, L.
Abstract: Background: The parallel decline of mobility and cognition with ageing is explained in part by shared brain structural changes that are related to fitness. However, the temporal sequence between fitness, brain structural changes and mobility loss has not been fully evaluated. Methods: Participants were from the Baltimore Longitudinal Study of Aging, aged 60 or older, initially free of cognitive and mobility impairments, with repeated measures of fitness (400‐m time), mobility (6‐m gait speed) and neuroimaging markers over 4 years ( n = 332). Neuroimaging markers included volumes of total brain, ventricles, frontal, parietal, temporal and subcortical motor areas, and corpus callosum. Autoregressive models were used to examine the temporal sequence of each brain volume with mobility and fitness, adjusted for age, sex, race, body mass index, height, education, intracranial volume and APOE ɛ4 status. Results: After adjustment, greater volumes of total brain and selected frontal, parietal and temporal areas, and corpus callosum were unidirectionally associated with future faster gait speed over and beyond cross‐sectional and autoregressive associations. There were trends towards faster gait speed being associated with future greater hippocampus and precuneus. Higher fitness was unidirectionally associated with future greater parahippocampal gyrus and not with volumes in other areas. Smaller ventricle predicted future higher fitness. Conclusion: Specific regional brain volumes predict future mobility impairment. Impaired mobility is a risk factor for future atrophy of hippocampus and precuneus. Maintaining fitness preserves parahippocampal gyrus volume. Findings provide new insight into the complex and bidirectional relationship between the parallel decline of mobility and cognition often observed in older persons. Abstract :